The Integral Membrane Protein Snl1p Is Genetically Linked to Yeast Nuclear Pore Complex Function - Ho, Albert K. (The American Society for Cell Biology, 1998)
Integral membrane proteins are predicted to play key roles in the biogenesis and function of nuclear pore complexes (NPCs). Revealing how the transport apparatus is assembled will be critical for understanding the mechanism of nucleocytoplasmic transport. We observed that expression of the carboxyl-terminal 200 amino acids of the nucleoporin Nup116p had no effect on wild-type yeast cells, but it rendered the nup116 null strain inviable at all temperatures and coincidentally resulted in the formation of nuclear membrane herniations at 23°C. To identify factors related to NPC function, a genetic screen for high-copy suppressors of this lethal nup116-C phenotype was conducted. One gene (designated SNL1 for suppressor of nup116-C lethal) was identified whose expression was necessary and sufficient for rescuing growth. Snl1p has a predicted molecular mass of 18.3 kDa, a putative transmembrane domain, and limited sequence similarity to Pom152p, the only previously identified yeast NPC-associated integral membrane protein. By both indirect immunofluorescence microscopy and subcellular fractionation studies, Snl1p was localized to both the nuclear envelope and the endoplasmic reticulum. Membrane extraction and topology assays suggested that Snl1p was an integral membrane protein, with its carboxyl-terminal region exposed to the cytosol. With regard to genetic specificity, the nup116-C lethality was also suppressed by high-copy GLE2 and NIC96. Moreover, high-copy SNL1 suppressed the temperature sensitivity of gle2–1 and nic96-G3 mutant cells. The nic96-G3 allele was identified in a synthetic lethal genetic screen with a null allele of the closely related nucleoporin nup100. Gle2p physically associated with Nup116p in vitro, and the interaction required the N-terminal region of Nup116p. Therefore, genetic links between the role of Snl1p and at least three NPC-associated proteins were established. We suggest that Snl1p plays a stabilizing role in NPC structure and function.